Electrodeposition of Ni-P/Ni-Co-Al2O3 duplex nanocomposite coatings: towards improved mechanical and corrosion properties. (1st November 2020) - Safavi, M. S.; Rasooli, A.; Sorkhabi, F. A.
ABSTRACT: Ni-Co alloy and composite coatings offer improved engineering properties such as hardness, wear resistance, and corrosion protection. The emphasis of this evaluation has been put on improvement of mechanical and corrosion properties of Ni-Co deposits by inclusion of the appropriate loadings of Al2 O3 nanoparticles along with deposition of Ni-P interlayer. For this goal, a broad range of Al2 O3 nanoparticles loadings, 0–80 g L −1, were incorporated into the Ni-Co alloy electrolyte to define precisely the optimum condition in terms of mechanical and corrosion performance. The inclusion of 60 g L −1 Al2 O3 nanoparticles enhanced the microhardness and charge transfer resistance of Ni-Co alloy deposit by 244 HV and ≈5 kΩ, respectively. The influence of Ni-P interlayer on the characteristics of the Ni-Co-60 g L −1 Al2 O3 coating was also assessed. A further increase in the abovementioned properties by 88 HV and ≈8 kΩ was obtained when a Ni-P interlayer was deposited between St 37 steel substrate and Ni-Co-60 g L −1 Al2 O3 coating.